2021
DOI: 10.31083/j.rcm.2021.01.216
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin converting enzyme inhibitors and angiotensin receptor blockers in acute heart failure: invasive hemodynamic parameters and clinical outcomes

Abstract: There are limited data regarding the use of angiotensin converting enzyme inhibitors/angiotensin receptor blockers (ACEi/ARBs) in acute heart failure (AHF). The purpose is to determine the patterns of ACEi/ARB use at the time of admission and discharge in relation to invasive hemodynamic data, mortality, and heart failure (HF) readmissions. This is a retrospective single-center study in patients with AHF who underwent right heart catheterization between January 2010 and December 2016. Patients on dialysis, evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Furthermore, in a separate single center study of 626 patients admitted with AHF, the major reasons for discontinuation of ACEI/ARB were similar with very low rates of hyperkalemia (2%). This was despite excluding patients on dialysis and those who presented with any type of shock [23]. In our study, in the multivariable analysis after adjusting for blood pressure and potassium levels, a perunit increase in admission SCr was independently associated with lower rates of continuation or initiation of ACEI/ARB, making renal function still the strongest predictor of ACEI/ARB utilization.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, in a separate single center study of 626 patients admitted with AHF, the major reasons for discontinuation of ACEI/ARB were similar with very low rates of hyperkalemia (2%). This was despite excluding patients on dialysis and those who presented with any type of shock [23]. In our study, in the multivariable analysis after adjusting for blood pressure and potassium levels, a perunit increase in admission SCr was independently associated with lower rates of continuation or initiation of ACEI/ARB, making renal function still the strongest predictor of ACEI/ARB utilization.…”
Section: Discussionmentioning
confidence: 61%
“…Mortality benefits were also seen on those discharged on ACEI/ARB with lower mortality risk at 30 days and 180 days, with HR 0.36, 95% CI (0. with the mortality benefit with maintenance of RAASi in AHF seen in the previous studies [5,24]. Another singlecenter analysis showed higher inpatient death and 6-month readmissions in patients with AHF with elevated RA pressures on right heart catheterization, who had ACEI/ARB discontinued or never initiated [23]. The protective effects with ACEI/ARB may reflect favorable modulation of the maladaptive RAAS in acute HF including in those with WRF from type 1 cardiorenal syndrome.…”
Section: Discussionmentioning
confidence: 76%
“…A previous study conducted in AHF patients revealed that one of the independent predictors of RAAS blocker discontinuation was worsening renal function and the use of RAAS blocker at admission was associated with less inpatient mortality. 39 In a recent study, less RAAS blocker usage was an independent risk factor for in-hospital mortality in the female group. Blood urea nitrogen level was higher in women also; however, higher level of it was found to be a predictor of mortality only in males.…”
Section: Discussionmentioning
confidence: 93%
“…To that end, the review by Singhania G et al on the continuation of renin angiotensin system inhibitors (RASi) in patients with acute heart failure (AHF) is an important contribution to the literature and emphasizes the need to ensure that vulnerable patients with AHF benefit from the continuation of GDMT, as well as appropriate decongestive therapies. Along the same vein, the manuscript by Lo KB et al [7] describes RASi usage patterns in AHF with data from right heart catheterizations delineating hemodynamic profiles in these patients and confirming the deleterious effects of persistent congestion and withdrawal of RASi in the setting of AHF, which include high rates of inpatient mortality as well as 6-month HF re-admissions. The management of HF in patients with ESKD assumes a higher level of complexity with challenges towards ascertaining an accurate diagnosis, implementing GDMT with limited high-quality data given exclusion of these patients from major RCTS in HF, and focusing on patient goals and quality of life.…”
mentioning
confidence: 90%